Railway in Nigeria : an insider's views - Osunbote, Oladele (Ibadan Text Pramark, 1997)
The book gives an insider's views on the various social and economic roles which the railways have played and can still play in Nigeria's developmental thrusts.
opc 31/08/16
Loans
Keywords: Railways; Rail transportation; Railways- Economic development; Nigeria